2013
DOI: 10.1016/j.jvir.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Prognostic Factors for Survival following Doxorubicin-eluting Bead Transarterial Chemoembolization for Hepatocellular Carcinoma

Abstract: Independent prognostic factors in patients with HCC undergoing DEB chemoembolization have been identified. Increased bilirubin level was not an independent risk factor. These data can be used in HCC patient selection and counseling for DEB chemoembolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
4
13
0
1
Order By: Relevance
“…The Child Pugh Class of HCC patient is considered to be the one of the main prognostic factors for survival following TACE in HCC patients. [24][25][26] In our study, there was a survival difference in the patients between Child A and B disease. However, statistically it was found nonsignificant.…”
Section: [17]mentioning
confidence: 43%
“…The Child Pugh Class of HCC patient is considered to be the one of the main prognostic factors for survival following TACE in HCC patients. [24][25][26] In our study, there was a survival difference in the patients between Child A and B disease. However, statistically it was found nonsignificant.…”
Section: [17]mentioning
confidence: 43%
“…Vesselle et al 19 revealed that tumor size was a negative predicitive factor for CR in HCC patients receiving DEB-TACE. Brown et al 20 and Sellers et al 21 showed that Child-Pugh stage was a negative predicitive factor for survival in HCC patients treated by TACE. Other factors, such as albumin-bilirubin, platelet-albumin-bilirubin grades, ECOG stage, BCLC stage, portal vein invasion, CA-199, Hb, ALP, ALB and AFP level, have also been proved to predict tumor response and survival.…”
Section: Discussionmentioning
confidence: 99%
“…TACE using DC Bead, drug-eluting microsphere (Biocompatibles UK Ltd, Farnham, United Kingdom), is a relatively novel modality related with favorable systemic doxorubicin exposure/toxicity and liver-specific toxicity compared to conventional TACE [26] . A recent study involving BCLC B HCC patients showed that DC Bead TACE resulted in a significantly better clinical outcome compared to conventional TACE [27] .…”
Section: Drug-eluting Bead Tacementioning
confidence: 99%
“…A recent study involving BCLC B HCC patients showed that DC Bead TACE resulted in a significantly better clinical outcome compared to conventional TACE [27] . However, Sellers et al [26] reported poor OS in HCC patients accompanying PVTT underwent DC Bead TACE. Further studies are warranted to evaluate the efficacy of DC Bead TACE and sorafenib in HCC patients accompanying PVTT.…”
Section: Drug-eluting Bead Tacementioning
confidence: 99%